Therapeutic outcomes and prognostic factors in patients with hypertrophic herpes simplex infection treated with imiquimod: A systematic review and meta-analysis of individual patient data from case reports and case series - Charussri Leeyaphan (2022)
Hypertrophic herpes simplex (HHS) often has atypical presentations, such as a hypertrophic mass or ulcers, with chronic courses. This situation poses a diagnostic challenge and results in delayed treatment. Imiquimod was used as a treatment for HHS by several studies, but the therapeutic outcomes varied. This systematic review and meta-analysis of individual patient data was conducted to investigate the therapeutic outcomes and prognostic factors of imiquimod treatment for patients with HHS. Biomedical databases (Embase, PubMed, Medline, Cochrane Controlled Trials Register, and ClinicalTrials.gov) were searched for all types of clinical studies reporting the complete cure rate and the time to complete response to imiquimod therapy between 1926 and 2021. Quantitative analysis of individual patient data was performed using multivariable flexible parametric survival regression with cluster variance correction. A total of 12 019 articles were identified and screened for eligibility. Twenty-five studies (21 case reports and four case series) with a combined total of 42 patients were included. The complete cure rate for imiquimod treatment was estimated at 88.1%. The median time to complete response was 60 days (95% confidence interval 35–70). Combined treatment, male sex, and an age less than 50 years were identified as significant prognostic factors for a shorter time to complete cure. A severe local reaction was reported in 2.3%. Imiquimod therapy has high effectiveness and safety in curing HHS. Patients who were male or younger than 50 years or whose treatments were combined with thymidine kinase-dependent antivirals had the best prognoses and were more likely to respond to treatment.